2019
DOI: 10.1101/564245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of new MmpL3 inhibitors by untargeted and targeted mutant screens defines MmpL3 domains with differential resistance

Abstract: 22combination studies of the inhibitors revealed interactions that were specific to the clades 40 identified in the cross-resistance profiling. Additionally, modeling of resistance substitutions to 41 the MmpL3 crystal structure revealed clade specific localization of the residues to specific 42 domains of MmpL3, with the clades showing differential resistance. Several compounds 43 exhibited high solubility and stability in microsomes and low cytotoxicity in macrophages, 44supporting their further development.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…These mutations likely weaken the affinity of antitubercular drugs targeting the transmembrane site, as has been demonstrated for a handful of Msmg MmpL3 variants by MST ( Zhang et al., 2019 ). This conclusion is also consistent with proposals that the magnitude and spectrum of the resistance phenotype given by an MmpL3 mutant correlates with its proximity to this pocket ( Williams et al., 2019 ). However, our analysis reveals that a significant proportion of RPs are located >10 Å away from the drug pocket, including some within the LMNG binding site (asterisks in Figure 2 A), suggesting that there is at least one additional, and as yet uncharacterized, MmpL3 resistance mechanism; likely involving the PD and its cavity.…”
Section: Resultssupporting
confidence: 92%
“…These mutations likely weaken the affinity of antitubercular drugs targeting the transmembrane site, as has been demonstrated for a handful of Msmg MmpL3 variants by MST ( Zhang et al., 2019 ). This conclusion is also consistent with proposals that the magnitude and spectrum of the resistance phenotype given by an MmpL3 mutant correlates with its proximity to this pocket ( Williams et al., 2019 ). However, our analysis reveals that a significant proportion of RPs are located >10 Å away from the drug pocket, including some within the LMNG binding site (asterisks in Figure 2 A), suggesting that there is at least one additional, and as yet uncharacterized, MmpL3 resistance mechanism; likely involving the PD and its cavity.…”
Section: Resultssupporting
confidence: 92%
“…In Mycobacteria, two independentlysynthesized fatty acids, the short alpha branch (C24-C26) and long meromycolate chain (C50-C60), produced by the single FAS-I enzyme and FAS-II complex (12,13), respectively, are modified then condensed by the cytoplasmic polyketide synthase, Pks13 (14), to form a 2alkyl 3-keto fatty acid which is then reduced by CmrA to generate the mature, hydroxylated mycolic acid (15). These fatty acids are conjugated to trehalose to form TMM which is then bound and flipped to the periplasm by the integral membrane lipid transporter MmpL3 (16,17), the target of several classes of new antimycobacterial inhibitors (18,19). While structurally diverse classes of MmpL3 inhibitors have been reported, several of these compounds were subsequently found to indirectly inhibit MmpL3, by disrupting the transmembrane electrochemical proton gradient (20).…”
Section: _____________________________________mentioning
confidence: 99%
“…Compound HC2091 (Figure 10) was originally identified as an inhibitor of M. tuberculosis in vitro (bactericidal activity) and in macrophages (bacteriostatic activity) by Zheng et al 207 It was reported in the same study that the compound inhibits the mycolic acid transporter, MmpL3. In another screening, HC2091 displayed almost 97% growth inhibition of M. abscessus at 20 μM (MIC 50 ~6.25 μM) in vitro 208 . In addition, William et al noted that HC2091 is not cytotoxic and exhibits good solubility and favorable microsome stability.…”
Section: Interesting Early‐stage Small Molecules Active Against M Abscessus: From Bench To Bedside?mentioning
confidence: 99%